AKTIVITAS ANTIOKSIDAN ANTOSIANIN DALAM EKSTRAK ETANOL KULIT BUAH NAGA SUPER MERAH (Hylocereus costaricensis) DAN ANALISIS KADAR TOTALNYA - Ni Ketut Meidayanti Putri; I Wayan Gede Gunawan; I Wayan Suarsa (Jurnal Kimia (Journal of Chemistry), 2015)
Dragon fruit is a plant that comes from dry tropical climate zones. Besides the flesh of the dragon fruits,,its skin can be used in food production as a natural food coloring and as the raw materials in cosmetics manufacturing. This is because of that the skin of the dragon fruit contains some compounds such as anthocyanin that can be used as an antioxidant. This study were aimed to determine the antioxidant activity,  total anthocyanin content and the type of anthocyanins in the ethanol extract of super red dragon fruit skin. The determination of antioxidant activity of anthocyanin was carried out by the use of DPPH method, whereas the determination of the total content of anthocyanin was performed with a pH difference method using UV-Visibel spectrophotometer. The results showed that the optimum scavenger percentage of the extract was of 97.84% with IC50 value of 73.2772 mg / L, whereas the average levels of total anthocyanins obtained was of 58.0720 ± 0,0001mg / L. The type of anthocyanins contained in the ethanol extract of the skin of super red dragon fruit was sianidin showing a maximum peak at a wavelength of 547 nm.